Umbilical pilonidal sinus in a teenager: A case report - Lillian Hsu; Aaron Payne Lesher (Elsevier, 2023)
The umbilical pilonidal sinus (UPS) is an uncommon clinical entity and, as such, is not easily diagnosed unless there is a high index of suspicion. Though pilonidal sinuses are most frequently seen around the gluteal cleft in adolescence, these lesions can occasionally be observed on other areas of the body, including the breast, spaces between the fingers, axilla, and umbilicus. UPS accounts for approximately .6% of all pilonidal disease1 and is one of the rarest subtypes. Known risk factors for UPS are similar to those for gluteal cleft pilonidal cysts and include young age, male, obesity, hirsuteness, and poor skin hygiene. We discuss a case of umbilical pilonidal sinus in a teenage male, which initially presented as an umbilical granuloma. After imaging was inconclusive, operative exploration revealed a hair-containing umbilical pilonidal sinus. An increased awareness of UPS among general pediatric surgeons may expedite clinical diagnosis and treatment and help to avoid low yield imaging tests.